Inhuman writing in Jeff VanderMeer's Southern Reach trilogy. Issue 8 (2nd August 2020) - Strombeck, Andrew
ABSTRACT: Jeff VanderMeer's Southern Reach trilogy, which has become well-known for its embrace of the nonhuman, is nevertheless highly interested in texts, literary and otherwise. VanderMeer has identified a key passage from the novel as originating in a dream he had after the Deepwater Horizon spill. He thus figures the spill as writing through him, a figuration which the series itself takes up. Moving from the dream writing, through scientific journals, through the agency designed to manage Area X, the series figures Area X as emanating what Bruno Latour has called beings of fiction. VanderMeer characterises, then, that which is unrepresentable in text as nevertheless representing itself in text, raising intriguing problems with the discourses – object oriented ontology and new materialism – that have often framed discussions of his novels.